Evaluation of Dolichos Genotypes (Dolichos lablab L.) under Northern Telangana Zone - R., Preetham; V., Suchitra; P., Saidaiah; A., Nithish (International Journal of Bio-resource and Stress Management, 2020)
A field trial was conducted at Horticultural Research Station, Adilabad of Northern Telangana Zone in Telangana State, India for two consecutive years of 2018 and 2019 with forty five genotypes of dolichos bean. The study was initiated to study the vegetative, floral characters and yield performance of different genotypes. The experiment was laid by adopting Randomized block design with two replications each in 2018 and 2019. Significant variations were noticed in the vegetative, floral characteristics; yield attributes and yields among the different genotypes. Stem pigmentation varied from meager or no pigmentation in 33 genotypes to almost solid in IC-426968 and IC-427428. The leaf colour was green and dark green in 12 and 33 genotypes respectively. The leaf shape was round (IC-426968), lanceolate, ovate lanceolate and ovate in 2, 10 and 32 genotypes. The standard petal colour and keel petal colour varied among the genotypes. It was cream, pink, purple and white. Maximum pod length was reported by IC-427436 and IC-427462 (16.15 cm), mean pod width by PSRJ-12953 (6.36 cm), mean pod weight by IC-427436 (11.05 g) and number of seeds per pod (6.35) by genotype Sambram. The genotype IC-427436 recorded significantly higher pod yield per plant (2713 g) and pod yield per hectare (13563 kg) over rest of the genotypes and it was followed by the genotypes IC-427462 and RND-1.